Sermons preached at the dedication of the Broadway Tabernacle, New York, Sunday, April 24, 1859...: to which are added Historical sketches of the Broadway Tabernacle and a formal dedication of the house (N.A. Calkins, 1859)
1. The prominence of the atonement / E.A. Park -- 2. The assembly of Christians the temple of God / R.S. Storrs -- 3. Preaching the gospel the grand function of the minister / J.P. Thompson.